Etiology of anemia of blood donor candidates deferred by hematologic screening - da Silva, Michel Alves (Associação Brasileira de Hematologia e Hemoterapia, 2012)
OBJECTIVE: Iron deficiency is the most common cause of anemia and one of the main factors in the clinical deferral of blood donors. This fact prompted the current study that aimed to determine the prevalence and etiology of anemia in blood donor candidates and to evaluate the hematological screening technique used for the exclusion of these donors. METHODS: This was a prospective study that compared two groups (Anemic and Non-anemic). Initially screening for anemia was performed by manually measuring hemoglobin (Bioclin(®) Kit); the results were subsequently compared with an automated screening method (Coulter T-890). The etiology was investigated by hemoglobin electrophoresis in alkaline and acid pH, Hb A2 dosage and measurement of the ferritin concentration by immunoagglutination. Differences and associations of interest were analyzed using the Yates and McNemar's Chi-square tests and the Fisher, Mann-Whitney, Wilcoxon and Kruskal-Wallis tests. RESULTS: The deferral rate due to anemia was 4.2%; iron deficiency was identified in 37.5% and beta thalassemia in 9.3% of the excluded candidates. There was a significant discrepancy between the two techniques used to measure hemoglobin with 38.1% of initially deferred donors presenting normal hemoglobin levels by the automated method. CONCLUSION: The results show a high rate of blood donors being deferred for anemia and confirm that iron deficiency is the most prevalent cause. The discrepancies found by comparing screening methods suggest that hemoglobin and hematocrit levels should be confirmed before deferring a donor due to anemia; this may increase supplies in blood banks.